Implementation of corporate social responsibility based on the triple bottom line concept in the era of Covid 19 pandemic - Gugus Wijonarko; Sri Juni Woro Astuti (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
In the age of the COVID-19 pandemic, the practice of corporate social responsibility (CSR) as a form of corporate focus on the corporate environment is necessary to reduce the financial burden on communities. Pelindo III, one of Indonesia's state-owned enterprises, implements its corporate social responsibility through a community empowerment program for hydroponic farmers in Surabaya. The assistance provided is not only in the form of funds for the procurement of hydroponics infrastructure and facilities, but also for administrative and financial management training, marketing and packaging. This study aims to describe how Pelindo III can implement CSR concepts and models in sustainable community empowerment, and to disseminate the CSR implementation model so that it can be replicated in other community empowerment programs. This study uses a descriptive qualitative approach and presents a case study of Pelindo III implementing CSR in a hydroponic farming community in Surabaya. The results of this study show that Pelindo III applies the principles of balancing and normative truth: sustainability, accountability and transparency, marked by a commitment to upholding the social contract. through this community development program. Pelindo III uses business ethics as a guide to its conduct in business competition in accordance with the normative norms and rules. Along the way, Pelindo III is faced with not just single bottom line (SBL) or only economic (financial)-based corporate value responsibilities, but more triple bottom line (TBL) responsibilities. Synergize three elements, including economy, society and environment, or better known as the 3Ps (profit, people and planet).